Pengaruh Video Penuntun Praktikum Terhadap Penguasaan Konsep dan Keterampilan Laboratorium Siswa SMA pada Materi Fotosintesis - Neiha Aisyah Nurfadillah; Sariwulan Diana; Bambang Supriatno (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – Many students experience difficulties in conducting laboratory experiments because pre-laboratory preparation is often ineffective. This condition may hinder students in carrying out laboratory activities and connecting experimental results with the concepts they have learned. Therefore, alternative pre-laboratory activities are needed to support students’ conceptual understanding and laboratory skills. This study examined the use of pre-laboratory videos in photosynthesis laboratory activities. Methods – This study used a pre-experimental method with a one-group pretest-posttest design. The participants were 35 students selected through purposive sampling. The instruments included a conceptual mastery test, a laboratory skills assessment, an observation sheet, and a Likert-scale student response questionnaire on the use of pre-laboratory videos. The data were analyzed using N-Gain analysis and the Wilcoxon signed-rank test. Findings – The results showed an increase in students’ conceptual understanding, with an N-Gain score of 0.77, which was categorized as high. The Wilcoxon signed-rank test indicated a significant difference between the pretest and posttest scores (p < 0.05). Students’ laboratory skills also improved, with an N-Gain score of 0.54. In addition, students gave positive responses to the use of pre-laboratory videos in laboratory activities. These findings indicate that pre-laboratory videos may support students’ conceptual understanding and laboratory skills in photosynthesis experiments.Research Implications – Since this study used a pre-experimental design without a control group, the findings should be interpreted with caution. The results indicate improvement after the use of pre-laboratory videos, but they do not provide strong evidence of a causal relationship. Further studies involving a control group are needed to examine the effectiveness of pre-laboratory videos more rigorously.